ECOCRITICISM DISCOURSE IN CLOUDY WITH A CHANCE OF MEATBALLS 2 MOVIE - Neisya, Neisya; Muhammad Fitriansyah, Abdillah; Aprilia, Fitria (Jurnal Ilmiah Bina Bahasa, 2024)
The ecological theme in literary works is continuing become a popular discourse to increase public awareness about the importance of protecting earth. Animated films are one of the medias for introducing this theme to people, especially children, because it can educate them in an easier way and more interesting. This research endeavors to explore the ecological dimensions and ethical reflections intertwined within the animated film "Cloudy with a Chance of Meatballs 2." Employing a descriptive qualitative research methodology, this research contributes to the broader discourse on ecocriticism and cinematic narratives by unveiling the ecological and ethical facets woven into film. Through this exploration, the study seeks to illuminate the film's role in shaping cultural attitudes towards nature, technology, and the delicate dance between humanity and the environment. Data were taken by watching the movie, citing the narrations and dialogues, as well as capturing scenes related to the environmental issue. Moreover, through the lens of eco-criticism perspective, the researchers interpret visual metaphors, character dynamics, and narrative layers to unravel the intricate ecological insights embedded within the film. The study contemplates the potential of animation as an eco-educational medium, discussing its impact on fostering environmental consciousness among audiences.